The experience of cranioplasty outcome, management and its complication in neurosurgery - Aurangzeb Kalhoro; Lal Rehman; Abdul Samad Panezai; Sher Hassan; Farrukh Javeed (International Journal of Endorsing Health Science Research, 2022)
Background: Head trauma is the most common case encountered in neurosurgery, and it is on the rise daily; head trauma sometimes requires the removal of skull bone which leads to another set of complications and associated issues related to cranioplasty. The study's objective was to share the single-center tertiary care hospital experience of cranioplasty, including outcomes, management, and associated complications.